2020
DOI: 10.3724/sp.j.1249.2020.03257
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prevention measures in Shenzhen based on SIQR model during the novel coronavirus pneumonia

Abstract: This paper proposes a joint gain and input design method for observer-based asymptotic active fault diagnosis, which is based on a newly-defined notion named the excluding degree of the origin from a zonotope. Using the excluding degree, a quantitative specification is obtained to characterize the performance of set-based robust fault diagnosis. Furthermore, a single gain design method and a joint gain and input design method are proposed, respectively. This is the first work to achieve a joint observer gain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…ID can also be a part of the containment measures during public health crises (Fu et al, 2020). In addition to aggregate statistics such as the total number of infected cases and the death toll, information about individual cases of infection can be released to the public with varying degrees of details (Fu et al, 2020;Jung et al, 2020;Xu et al, 2020). In the case of COVID-19, one study shows that the disclosure of details about confirmed cases such as their travel history, activities, and visible symptoms may alert and prompt people with close contact to undergo testing and self-quarantine (Smith et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…ID can also be a part of the containment measures during public health crises (Fu et al, 2020). In addition to aggregate statistics such as the total number of infected cases and the death toll, information about individual cases of infection can be released to the public with varying degrees of details (Fu et al, 2020;Jung et al, 2020;Xu et al, 2020). In the case of COVID-19, one study shows that the disclosure of details about confirmed cases such as their travel history, activities, and visible symptoms may alert and prompt people with close contact to undergo testing and self-quarantine (Smith et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%